2014
DOI: 10.1038/srep05728
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of planktonic methane-oxidizing bacteria in a subtropical reservoir characterized by dominance of phylotype closely related to nitrite reducer

Abstract: Methane-oxidizing bacteria (MOB) gain energy from the oxidation of methane and may play important roles in freshwater ecosystems. In this study, the community structure of planktonic MOB was investigated in a subtropical reservoir. Bacterial community structure was investigated through the analysis of the 16S rRNA gene. Three groups of phylogenetically distinct MOB were detected in the clone libraries of polymerase chain reaction products obtained with universal primers. The groups belonged to the class Gammap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…The probes DBACT-1027 and Mα450 perfectly match all 16S rRNA sequences of targeted MOB, detected in the clone libraries of the water from FTR (Kojima et al 2014). On the other hand, probes Mγ84 and Mγ705 have mismatches to some type I MOB detected in the FTR, and these MOB might have been missed with the probes.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The probes DBACT-1027 and Mα450 perfectly match all 16S rRNA sequences of targeted MOB, detected in the clone libraries of the water from FTR (Kojima et al 2014). On the other hand, probes Mγ84 and Mγ705 have mismatches to some type I MOB detected in the FTR, and these MOB might have been missed with the probes.…”
mentioning
confidence: 87%
“…In fact, predominance of the M. oxyfera -like MOB over proteobacterial MOB has hardly ever been reported, except for in cultures designed specifically to enrich them. In a previous study performed in a subtropical reservoir, high relative abundance of the M. oxyfera -like phylotype within the bacterial community was observed in the deep waters of a subtropical reservoir that was characterized by anoxic conditions (Kojima et al 2014). In the reservoir, Feitsui Reservoir (hereafter, FTR) in Taiwan, a close relative of M. oxyNote fera was the most frequently detected species-level phylotype among planktonic MOB detected using 16S rRNA gene sequences (Kojima et al 2014).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Long-term monitoring of methanotrophic food webs is of ecological importance in understanding how carbon cycling is altered in lakes affected by anthropogenic activities. In the FTR, it has been reported that MOBs dominate profundal bacterial communities, showing remarkable vertical and seasonal variations in community compositions (Kojima et al, 2014;Kobayashi et al, 2016). Itoh et al (2015) experimentally demonstrated that the methane oxidation activity is highest in deep sub-oxic layers, in which both dissolved methane and oxygen are available to MOBs.…”
Section: Pelagic and Profundal Food Websmentioning
confidence: 99%